2016
DOI: 10.3389/fmolb.2016.00055
|View full text |Cite
|
Sign up to set email alerts
|

Glycation in Demetalated Superoxide Dismutase 1 Prevents Amyloid Aggregation and Produces Cytotoxic Ages Adducts

Abstract: Superoxide dismutase 1 (SOD1) has been implicated with familial amyotrophic lateral sclerosis (fALS) through accumulation of protein amyloid aggregates in motor neurons of patients. Amyloid aggregates and protein inclusions are a common pathological feature of many neurological disorders in which protein aggregation seems to be directly related to neurotoxicity. Although, extensive studies performed on the aggregation process of several amyloidogenic proteins in vitro allowed the identification of many physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…In our study, MGO concentrations of 100 μM and 1 mM are effectively glycating SOD1. At the latter MGO concentration, SOD1 oligomerization is observed, confirming an earlier result by the Iannuzzi lab [24] (Fig 6).…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, MGO concentrations of 100 μM and 1 mM are effectively glycating SOD1. At the latter MGO concentration, SOD1 oligomerization is observed, confirming an earlier result by the Iannuzzi lab [24] (Fig 6).…”
Section: Plos Onesupporting
confidence: 91%
“…In contrast, glycation with a high level of MGO (1 mM) leads to the appearance of an additional maximum at approximately 66˚C and a slight shift of the main maximum to 90˚C. The former peak might be based on a de-metallated form of the protein (i. e., apoSOD1) that is present in the sample whereas the latter indicates a slightly stabilizing effect of MGO on SOD1 which was reported previously [24] and which we could demonstrate by immunodetection ( Fig 2B). The pronounced aggregation of SOD1 Table 2.…”
Section: Structural Element α-Helix β-Strand Turns Unorderedsupporting
confidence: 59%
See 1 more Smart Citation
“…Cells in culture medium without protein and in the presence of curcumin and vanillin at the tested concentrations served as control. In the AGE experiments, before cells exposure, insulin glycated in the presence of 0.5 M D-ribose for 8 days was subjected to dialysis in sterile conditions to remove the free glycating agent 89 .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, SOD1 is an extremely stable protein when fully assembled, but it is rather unstable and prone to aggregation in its metal-free form. Many studies have shown that wild-type human SOD1, when lacking both its metal ions, forms large and stable amyloid-like protein aggregates under physiological conditions of pH and temperature thus suggesting that metal binding could play a key role in the in vivo aggregation process of SOD1 [ 15 , 24 , 25 , 26 , 27 , 28 , 29 ]. Moreover, it has been reported that also some SOD1 mutants, many of them related to familial ALS, form amyloid aggregates both in vitro and in vivo and that demetalation is the key factor for aggregation [ 15 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%